Accommodating Islamic Worship Practices for Stoma Patients: A Comprehensive Systematic Review - Faiz, Muhammad (University of Muhammadiyah Semarang, 2023)
This systematic review explores the challenges and accommodations necessary for stoma patients practicing Islamic worship, focusing on ritual purity (tahara) and prayer (salat). The review synthesizes findings from recent studies to identify effective strategies for healthcare providers to support Muslim stoma patients. The analysis includes religious guidance, patient perspectives, and practical recommendations for managing stoma care in the context of Islamic rituals. The findings highlight the importance of culturally sensitive care and suggest specific modifications to enhance the religious and spiritual well-being of Muslim stoma patients